2013
DOI: 10.4103/0300-1652.119657
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitude towards child adoption among women in Zaria, northern Nigeria

Abstract: Background:The success of marriages has largely been premeditated on child bearing in most African society and oftentimes women are at the receiving end of childlessness with possible psychological and physical torture.Objective:To assess the knowledge and attitude of women of reproductive age towards child adoption in Zaria, Northern Nigeria.Methodology:A cross-sectional descriptive study, structured closed and open ended questionnaires was administered to 200 consenting consecutive women aged 15–49years to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 10 publications
2
10
1
Order By: Relevance
“…It was however revealed that despite a good knowledge of the meaning of adoption, only 38.1% of respondents knew what the process of adoption entails, though the majority (65.7%) are aware that there are established laws governing child adoption. These findings agreed with those from other studies in Sokoto and Zaria both in NorthWest Nigeria [12,13]. One can safely conclude that from both Northern and Southern divides of the country, though child adoption may have been unpopular in traditional African Societies, it is not a new concept to the people of Nigeria.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It was however revealed that despite a good knowledge of the meaning of adoption, only 38.1% of respondents knew what the process of adoption entails, though the majority (65.7%) are aware that there are established laws governing child adoption. These findings agreed with those from other studies in Sokoto and Zaria both in NorthWest Nigeria [12,13]. One can safely conclude that from both Northern and Southern divides of the country, though child adoption may have been unpopular in traditional African Societies, it is not a new concept to the people of Nigeria.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, all the respondents reported to have heard of adoption, and 91.8% of them knew the correct meaning of child adoption. This is consistent with the finding from a study carried out in Zaria, North-West Nigeria, were 89.4% of the respondents knew the meaning of child adoption [12]. This is however in contrast with the finding in another study carried out in Lagos University teaching hospital, South-West, Nigeria was only a little above half of the respondents (59.3%) knew the correct meaning of child adoption [1].…”
Section: Discussionsupporting
confidence: 88%
“…nfertility as a life crisis, accompanies with a vast range of social, psychological, physical, and financial problems (Avidime et al 2013;Greil et al 2010). More than 80 million people worldwide are infertile.…”
Section: Introductionmentioning
confidence: 99%
“…Avidime et al [13] found that 77% had good attitudes towards adoption and that there was an association between the number of living children and the desire to adopt a child. Adewunmi et al [8] found that 42.6% of the patients wanted the option of adoption only if there was no solution to the infertility.…”
Section: Discussionmentioning
confidence: 99%